Elevation of serum human epididymis protein 4 (HE4) and N-terminal pro-B-type natriuretic peptide (NT-proBNP) as predicting factors for the occurrence of acute kidney injury on chronic kidney disease: a single-center retrospective self-control study - Song, Jinye; Chen, Ling; Yuan, Zheping; Gong, Xuezhong (Frontiers in Pharmacology, 2023)
Objectives: To evaluate whether novel biomarkers of renal injury, serum HE4 and NT-proBNP could predict acute kidney injury (AKI) on chronic kidney disease (CKD) (A on C) and assess the specificity and efficiency of serum creatinine (SCr), HE4 and NT-proBNP in identifying potential AKI. Meanwhile, the potential early-warning value of HE4 and NT-proBNP in CKD patients was explored. Methods: We performed a single-center, retrospective cohort study of 187 adult CKD patients. 32 AKI (grades 1–2) patients with pre-existing CKD (stages 3–5) were Group 1, 59 patients of CKD (stages 4–5) were Group 2. Another 96 patients of CKD (stages 1–3) were Group 3. All patients received general treatments, Group 1 patients received Chinese herb formulation (Chuan Huang Fang-Ⅱ, CHF-Ⅱ) simultaneously. These 155 CKD (stages 1–5) without AKI patients were observed for descriptive analysis. Results: HE4 in Group 1 (860.63 ± 385.40) was higher than that in Group 2 (673.86 ± 283.58) before treatments. BUN, SCr, UA, NGAL, IL18, HE4 and NT-proBNP in Group 1 were lower, while eGFR was higher (p < 0.01, after vs. before treatments). In Group 1, both HE4 and NT-proBNP were positively correlated with SCr (respectively r = 0.549, 0.464) before treatments. The diagnostic performance of serum HE4 and NT-proBNP for A on C was 351.5 pmol/L, 274.5 pg/mL as the optimal cutoff value Area Under Curve (AUC) 0.860 (95% CI: 0.808 – 0.913, p < 0.001), [AUC 0.775 (95% CI: 0.697 – 0.853, p < 0.001), with a sensitivity and specificity of 100% and 66.5%, 87.5% and 48.8%, respectively]. In Group 2, serum HE4 was correlated with SCr (r = 0.682, p < 0.01) before treatments. Serum HE4 and NT-proBNP were elevated in advanced CKD stages, and were increased as CKD stages progressed with statistical significance. Conclusion: This work indicated serum HE4 and NT-proBNP should elevate in A on C and CKD patients, HE4 is positively correlated with the disease severity, and patients with higher HE4 and NT-proBNP usually have poorer prognosis. Thus, serum HE4 and NT-proBNP are impactful predictors of A on C. Additionally, serum HE4 and NT-proBNP have the potential to evaluate clinical efficacy of A on C.